LAW ENFORCEMENT AGAINST CIVIL SERVANTS WHO CONDUCT THE VIOLATION – TOWARD IMPLEMENTATION OF GOOD GOVERNANCE - Amsarno S. Sarumaha; Maidin Gultom; Solistis Dachi (JURNAL PROINTEGRITA, 2019)
The purpose of this study is to find out, analyze and understand the procedures and mechanisms that are implemented in the implementation of good governance and good governance, the efforts undertaken by the government in improving the understanding of all components of stakeholders about good governance abd law enforcement against the civil servants who commit criminal acts. The data used in this study are primary data and secondary data. Primary data were obtained from the field by conducting interviews and case studies with related parties. Secondary data obtained through library research or documentation.Through this research obtained thoughts, doctrines, opinions or conceptual thoughts from previous studies relating to the object of research research In conducting research used legal materials consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The results showed that the procedures and mechanisms that are implemented in the implementation of good governance and good governance are the implementation of good governance, clean and authoritative sustainable development and social justice, functional aspects of government that are effective and efficient in making efforts to achieve national goals. The orientation of good governance is: ideal state orientation directed towards the achievement of national goals. This orientation refers to democratization in the life of the state with its constituent elements, such as: legitimacy (whether the government is elected and has the trust of its people, accountability, securing of human rights, autonomy und devolution of power, and assurance of civilian control. A functioning government ideal, that is, effective, efficient in making efforts to achieve rational goals.This orientation, depends on the extent to which the government has competence and the extent to which political and administrative structures and mechanisms function effectively and efficiently.The efforts that must be made in increasing understanding of all components stakeholders about good governance.To achieve the socio-economic conditions above, the process of forming a democratic government is absolutely necessary. management of state institutions, good and clean governance can be realized maximally if it is supported by two interrelated elements: the state and the Civil Society in which there is a private sector. Countries with their government bureaucracy are required to change the pattern of public services from an elitist bureaucracy perspective into a populist bureaucracy. Populist bureaucracy is governance that is oriented towards serving and siding with the interests of society. Realizing the principles of good and clean governance, regional autonomy policy can be used as a medium for the transformation of the realization of the model of governance that sustains the growth of democratic culture in Indonesia.